Persepsi Mahasiswa Terhadap Peran dan Tanggung Jawab Auditor. Study Experimen Pada Mahasiswa Panca Marga Probolinggo - Saifullah - (Ecobuss, 2015)
This paper excamines the effect of education on students perceptions of the meaning of audit repots and responsibilities and duties of auditors. A research instrument, utisising semantic differential scales designed to measure the messages communicated through audits reports, was administered to two groups of undergraduate students at the beginning and end of a semester. The experimental group consisted of final year under graduate accounting students enrolled in their first auditing unit. The control group co nsisted final year under graduate manajement students not enrolled in auditing unit. There are 40 manajement participated in the experiment anf there are 40 manajement students participated in the control at the beginning of a semester. The same students are used at the end of a semester, Mann Whitney U test was used to test hypotheses one, two and three. Kruskall-Wallis One-Way Analysis of Variance was used to test for differences in responses between the relative responsibilities at auditors and prapares of financial repots (responsibility), the reliability of financial information (realiability) and the evaluation of the future prospects of the firm (prospects). The results of the experiment confirm the hypotheses proposed. So the results of the study suggest that education may be an affec tive approach to narrowing or eliminating the audit expectation gap. This research has implication that happen the expectation gap, but the gap’s can be reduced by auditing education program. Key Words : Perception, responsibility and duty of auditor’s, audit repots, expectation gap.